A case report of severe acute pancreatitis with infected necrosis and concomitant Coronavirus Disease‑19 (COVID‑19): a nosocomial infection or delayed respiratory manifestation of viral disease? - Susak, Y.; Tkachenko, O.; Lobanova, O.; Skivka, L. (General Surgery, 2021)
The association between COVID‑19 and acute pancreatitis (AP) has been extensively analyzed in recent research and review papers worldwide. It should be noted that most studies have focused on AP as a COVID‑19 complication and/or an extra‑pulmonary manifestation of the disease, although the investigation reports on the cases of prior pancreatitis and subsequent COVID‑19 infection are limited. The aim of this case report is to describe the treatment protocol and clinical outcome of a patient with acute necrotizing pancreatitis who developed nosocomial COVID‑19.. Case presentation. The data were collected from patient S., a 42‑year‑old male admitted with AP to the intensive care unit of Kyiv City Clinical Emergency Hospital, in October 2020. This study was reviewed and approved by the local Ethics Committee (Protocol No 25‑15‑60). The patient signed written informed consent to participate in the study, after having been informed of all relevant aspects that could influence his decision. The patient, primarily diagnosed with AP, was admitted to the hospital without a PCR test for detecting SARS‑CoV‑2. 21 days after his admission to the hospital, the patient developed COVID‑19. AP progression to severe AP with infected necrosis, the development of systemic inflammatory response syndrome and multiple organ failure necessitated operative pancreatic debridement, which was postponed due to severe acute respiratory failure. Operative pancreatic debridement was performed on the 45th day of hospital stay after the resolution of COVID‑19‑associated pneumonia. The postoperative period was typical for the disease severity and the extent of the surgery, and was complicated by external pancreatic and colonic fistulas. The length of hospital stay for this patient was 115 days which included 20 days of treatment and monitoring in the intensive care unit due to pneumonia. He was discharged after clinical symptom improvement. Conclusions. It is imperative to screen patients presenting with AP for SARS‑CoV‑2 in order to avoid misdiagnosis and inappropriate treatment strategy. Further detailed investigation of mechanisms of pancreatic injury in patients with SARS‑CoV‑2 is necessary.